Postmodern and postcolonial elements in Leonard Cohen`s oeuvre - Adamskich, Karolina (Scripta Neophilologica Posnaniensia, 2022)
The article, apart from examining briefly the reception of Leonard Cohen`s art and persona by the critics, presents him also as a writer preoccupied with ethical issues. It will be demonstrated that, along with creating his own eclectic spiritual system by synthesizing elements borrowed from different religions and wisdom traditions, Cohen has been also influenced by the socio-political situation in Canada and worldwide. Hence, Cohen`s art will be discussed in relation to the post-Holocaust reality, the Quiet Revolution in Quebec, the sexual liberation, the process of Canada becoming a “postmodern country”, as well as cultural changes, such as the shifting position of the popular culture. The article aims also at highlighting the postcolonial and postmodern elements in Cohen`s oeuvre, inasmuch as Cohen has been argued to be one of the first Canadian representatives of these literary trends.